Functionalization of 3D printed micro‐containers with Ni‐Au core‐shell nanowires. Issue 6 (24th February 2017) - Gill, Waqas Amin; An, Boo Hyun; Lee, Ji Sung; Ali, Dima; Khalil, Malathe Samir; Park, Jungrae; Choi, Young Soo; Kim, Young Keun; Choi, Daniel S.
Abstract : Three‐dimensional printing (3DP) technology has attracted interest in various fields of applications. However, most of the previous studies are focusing on additive printing or developing new printable materials to functionalize the printed structures. Those approaches obviously have shown great performance, but still have no solution to functionalize original printing materials that are supplied by printer suppliers. In this study, we report a feasible method to fabricate three‐dimensional printed micro‐containers (MCs) coated with Ni‐Au core‐shell nanowires (NWs) that have multifunctional properties. The surfaces of the polymer‐based micro‐containers are modified with thiol groups. Then Ni‐Au nanowires are directly attached without further treatment. Our approach expands direct applications of polymeric 3DP materials to biomedical and pharmaceutical technology as a utilized platform for functional nanostructures.